Fiber Lasers X: Technology, Systems, and Applications 2013
DOI: 10.1117/12.2004698
|View full text |Cite
|
Sign up to set email alerts
|

Multi-kW cw fiber oscillator pumped by wavelength stabilized fiber coupled diode lasers

Abstract: High power Yb doped fiber laser sources are beside CO 2 -and disk lasers one of the working horses of industrial laser applications. Due to their inherently given robustness, scalability and high efficiency, fiber laser sources are best suited to fulfill the requirements of modern industrial laser applications in terms of power and beam quality.Pumping Yb doped single-mode fiber lasers at 976nm is very efficient. Thus, high power levels can be realized avoiding limiting nonlinear effects like SRS. However the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 5 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…This is mainly driven by the significant advantages of diode lasers over their CO 2 laser counterpart, including the high material absorption and electro-optical conversion efficiency, etc. [4][5][6]. The output wavelengths of 9xx nm highpower diode lasers are shorter than that of CO 2 lasers.…”
Section: Introductionmentioning
confidence: 94%
“…This is mainly driven by the significant advantages of diode lasers over their CO 2 laser counterpart, including the high material absorption and electro-optical conversion efficiency, etc. [4][5][6]. The output wavelengths of 9xx nm highpower diode lasers are shorter than that of CO 2 lasers.…”
Section: Introductionmentioning
confidence: 94%
“…In recent years, with the improvement of Large Mode Area (LMA) gain fiber technology, high brightness semiconductor pump sources, and high-power fiber coupler devices, fiber lasers have continuously developed towards higher power and beam quality. The Yb-doped fiber (YDF) with LMA has shown tremendous progress in attaining kilowatt and even multi-kilowatt with near diffraction-limited beam quality [2][3][4][5]. Fiber lasers are widely used in industrial manufacturing, scientific research, national defense and military industry due to their high electro-optical conversion efficiency, good beam quality, simple thermal management, and ease of integration.…”
Section: Introductionmentioning
confidence: 99%
“…Because it has such a far-reaching impact, signal/pump wavelength [15][16][17][18][19][20][21], fiber coiling [22][23][24][25] and fiber parameters such as core/cladding size [19,[25][26][27][28][29] have been investigated to gain a deeper insight into MI. It has been reported theoretically and experimentally that the MI threshold is reduced when the total pump absorption is reduced by shortening the fiber length [21,28], which is one of the ways to suppress the pump power noise [14] and nonlinear effects [30].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported theoretically and experimentally that the MI threshold is reduced when the total pump absorption is reduced by shortening the fiber length [21,28], which is one of the ways to suppress the pump power noise [14] and nonlinear effects [30]. Previous research has confirmed that without accurate wavelength stabilization technology the pump wavelength changes during operation [31,32], which affects the optical-to-optical efficiency by changing the pump absorption [20]. For a fiber laser system pumped with an unstabilized laser diode, the pump…”
Section: Introductionmentioning
confidence: 99%